3 2 + 1 1 + 4 2 + 2 1 + 5 2 + 3 1 + 6 2 + 4 1 + ⋯
The series above can be expressed as n m , where m and n are coprime positive integers.
Find m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did it the same way, thumbs up +1
∑ n = 1 ∞ ( n + 2 ) 2 + n 1 = ∑ n = 1 ∞ n 2 + 4 n + 4 + n 1 = ∑ n = 1 ∞ ( n + 1 ) ( n + 4 ) 1 ∑ n = 1 ∞ − 3 ( n + 1 ) ( n + 4 ) − 3 + n − n = − 3 1 ∑ n = 1 ∞ − 2 ( n + 1 ) ( n + 4 ) ( n + 1 ) − ( n + 4 ) = − 3 1 ∑ n = 1 ∞ ( n + 4 1 − n + 1 1 ) = − 3 1 ( 5 1 + 6 1 + … − 2 1 − 3 1 − 4 1 − 5 1 − 6 1 − … ) = − 3 1 ( 2 1 − 3 1 − 4 1 ) = 4 1 ( 1 2 1 3 ) = 3 6 1 3 ∴ m + n = 4 9
oh good! and you nicely have written the solution.. I too am trying to write more in latex, cos I have not that much excellence in LATEX ;p
Log in to reply
Use this then : latex4technics.com
There are many websites which give you a user friendly latex-code.
Log in to reply
Good find!
Using WYSIWYG is a good way of gaining familiarity with Latex :)
Note: Be very careful with expanding out a summation and reordering terms. The way that you reordered it, you ended up with ∞ − ∞ which is undefined.
Problem Loading...
Note Loading...
Set Loading...
S = 3 2 + 1 1 + 4 2 + 2 1 + 5 2 + 3 1 + 6 2 + 4 1 + . . . = k = 1 ∑ ∞ ( k + 2 ) 2 + k 1 = k = 1 ∑ ∞ k 2 + 4 k + 4 + k 1 = k = 1 ∑ ∞ k 2 + 5 k + 4 1 = 3 1 k = 1 ∑ ∞ ( k + 1 1 − k + 4 1 ) = 3 1 ( 2 1 + 3 1 + 4 1 ) = 3 6 1 3
⟹ m + n = 1 3 + 3 6 = 4 9